Study of Sperm Utilization in Female Drosophila melanogaster of bdp and btx Strains - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study investigates the patterns of sperm utilization in female Drosophila melanogaster of the bdp and btx strains through sequential mating with multiple males. The research was conducted as a descriptive observational study without experimental manipulation. Females of each strain were crossed with four different males in a specific order, with a two-day interval between each mating. F1 offspring phenotypes were recorded daily over a six-day period following the final mating. Data were analyzed descriptively and supported by somatic chromosome reconstruction to identify the male origin of each offspring. The results indicate that sperm utilization in D. melanogaster females occurs in both random and non-random patterns. Non-random utilization was observed when offspring were produced exclusively from the first male, with no contribution from subsequent males. For example, in the female btx × male N cross, only N female and N male offspring were produced, indicating that sperm from the first male was preferentially used. In contrast, random sperm utilization was evident in later matings, where offspring from multiple males appeared, suggesting that previously stored sperm remained viable and were used alongside or instead of sperm from later matings. These findings highlight the complexity of post-mating sexual selection in D. melanogaster, particularly the role of female sperm storage and utilization mechanisms. The ability of females to either favor the sperm of a particular male or mix sperm from several males may provide evolutionary advantages in terms of genetic diversity and offspring fitness. This study contributes to a better understanding of reproductive strategies and sperm competition in insects, with potential implications for broader studies in evolutionary biology and genetics.